A note on the convergence rate of Kumar–Singh–Srivastava methods for solving nonlinear equations - J.P. Jaiswal (Journal of the Egyptian Mathematical Society, 2017)
In the present article, it is shown that both the methods presented in Kumar et al. (2013) do not possess the order of convergence as claimed. One of the two methods, derivative involved method possesses the convergence rate of eighth order whereas the other derivative free method possesses sixth order convergence. The theoretical convergence rate is also validated by computational order of convergence.